1991
DOI: 10.1128/mcb.11.1.289
|View full text |Cite
|
Sign up to set email alerts
|

The strong ADH1 promoter stimulates mitotic and meiotic recombination at the ADE6 gene of Schizosaccharomyces pombe.

Abstract: The effect of the strong promoter from the alcohol dehydrogenase gene on mitotic and meiotic intragenic recombination has been studied at the ade6 locus of the fission yeast Schizosaccharomyces pombe. A 700-bp fragment containing the functional adhi promoter was used to replace the weak wild-type promoter of the ade6 gene. Analysis of mRNA showed that strains with this ade6::adhl fusion construct had strongly elevated ade6-specific mRNA levels during vegetative growth as well as in meiosis. These increased lev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

4
49
0
1

Year Published

1991
1991
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(54 citation statements)
references
References 45 publications
4
49
0
1
Order By: Relevance
“…Eight crosses of 469 with M26 and four with M375 showed that the M26 hot spot had no detectable activity when the recombining ade6 genes were remote from their endogenous location ( Table 2, group C). [The 2-fold lower frequency with M26 than with M375 is within the range previously reported (2) (15). In our assays for M26 hot spot activity at ura4 the measured recombinant frequencies were lower than these values: 610 vs. 580 per 106 viable spores for M26 and M375, respectively, on the 0.35-kb insertions and 1900 vs. 3500 for M26 and M375, respectively, on the 3.0-kb insertions (Table 2, group B and group C).…”
Section: Resultssupporting
confidence: 72%
“…Eight crosses of 469 with M26 and four with M375 showed that the M26 hot spot had no detectable activity when the recombining ade6 genes were remote from their endogenous location ( Table 2, group C). [The 2-fold lower frequency with M26 than with M375 is within the range previously reported (2) (15). In our assays for M26 hot spot activity at ura4 the measured recombinant frequencies were lower than these values: 610 vs. 580 per 106 viable spores for M26 and M375, respectively, on the 0.35-kb insertions and 1900 vs. 3500 for M26 and M375, respectively, on the 3.0-kb insertions (Table 2, group B and group C).…”
Section: Resultssupporting
confidence: 72%
“…For the multiplicative function this was (1 Ϫ M ab ) 4 , the fraction of the population receiving no new mutations in each generation. This was identical to the viability of an asexual population and was not changed by recombination (compare lines 1, 2, and 3).…”
Section: Resultsmentioning
confidence: 99%
“…Most studies of the mechanism have been done in ascomycete fungi, where meiosis can be synchronously induced and all the meiotic products recovered in the ascus. Biased gene conversion is a typical consequence of recombination at hotspots (4)(5)(6). For example, a cross between active and inactive alleles of the ARG4 hotspot in the yeast Saccharomyces cerevisiae exhibits a 22-fold bias toward conversion of the active allele to its inactive homolog (6).…”
mentioning
confidence: 99%
“…One striking characteristic of hotspots is that they are subject to a form of meiotic drive: when a DSB occurs at a hotspot heterozygous for an active (''hot'') and an inactive (''cold'') hotspot allele, the cold allele tends to appear in a higher proportion of the offspring than does the hot allele (often in an $3:1 ratio rather than the expected 2:2) (Catcheside 1975;Nicolas et al 1989;Grimm et al 1991;Malone et al 1994;Guillon and De Massy 2002;Jeffreys and Neumann 2002;Jeffreys and May 2004;Cromie et al 2005). This is likely the result of the mechanism by which recombination is thought to be initiated: a doublestrand break (DSB) forms on one chromatid; this break extends a variable distance in the 59 direction on each strand; and the sequence of the nonsister chromatid is used as a template to repair the gap.…”
mentioning
confidence: 99%